Caveolin-1 promotes tumor growth and metastasis via autophagy inhibition in hepatocellular carcinoma - Liu, Wei-Ren; Jin, Lei; Tian, Meng-Xin; Jiang, Xi-Fei; Yang, Liu-Xiao; Ding, Zhen-Bin; Shen, Ying-Hao; Peng, Yuan-Fei; Gao, Dong-Mei; Zhou, Jian; Qiu, Shuang-Jian; Dai, Zhi; et al. (Clinics and research in hepatology and gastroenterology, 2016)
Caveolin-1 is a member of the caveolae family of membrane proteins. Although some researchers have investigated the function of Caveolin-1 in hepatocellular carcinoma, the mechanism of Caveolin-1 action and its prognostic value in hepatocellular carcinoma remain unclear. Caveolin-1 expression was measured in hepatocellular carcinoma cell lines and tissues using quantitative reverse transcription-polymerase chain reaction, western blot, and immunofluorescence assays. In in vitro experiments, Caveolin-1 was depleted using a short hairpin RNA lentiviral vector, and tumor cell behavior was analyzed. The effect of Caveolin-1 on hepatocellular carcinoma cell autophagy was investigated. Prognostic value of Caveolin-1 was analyzed by immunohistochemistry in two cohorts that included a total of 721 hepatocellular carcinoma patients. We found that Caveolin-1 was overexpressed in highly metastatic hepatocellular carcinoma cell lines and tumor tissues. Moreover, Caveolin-1 promoted hepatocellular carcinoma cell proliferation, migration, and angiogenesis and inhibited autophagy. Finally, Caveolin-1 expression in hepatocellular carcinoma tissues was inversely correlated with patient overall survival and time to recurrence. Our data obtained from cell lines suggest an oncogenic role for Caveolin-1 in hepatocellular carcinoma, Caveolin-1 contributed to hepatocellular carcinoma cell autophagy deficiency. Furthermore, Caveolin-1 may function as a novel prognostic indicator for hepatocellular carcinoma patients after curative resection, and combination of targeted therapy aimed at Caveolin-1 and autophagy modulation may represent an effective way to treat hepatocellular carcinoma.